Optimization of regional coverage satellite constellations based on ant colony algorithm - WEI Jiao-long; CEN Zhao-hui (Tongxin xuebao)
First,an optimization model of constellation parameters aimed at improving coverage performance was built.Second,defining the new strategy of sorting and transferring based on Continuous space,Ant colony algotithm（ACA）was improved,the particular case that multi-objects could not be compatible was also included,and an optimization framework was proposed.Finally,the simulation results demonstrate the effect of ACA,which can improve the efficiency of optimization.